Capital Market Development Practice in the Republic of Uzbekistan - Ph.D Azizbek Abdurashidovich Shomirov (Zien Journals, 2022)
The introductory part of this article presents the changes taking place in the Republic of Uzbekistan on the further development and regulation of the capital market, which is a key segment of the financial-credit system. Theoretical and scientific research of leading foreign and domestic economists on the economic nature of the capital market is studied. Segments of the capital market are considered, in particular, analytical data on international and national stock markets are presented. According to the author's position, the problems hindering the extensive development of the capital market are listed. The final part of the article contains conclusions and proposals for further development of the capital market.
Keywords: Financial-credit system; capital market; corporate structures; companies